Social Reactions and Women's Decisions to Report Sexual Assault to Law Enforcement. (April 2020) - DePrince, Anne P.; Wright, Naomi; Gagnon, Kerry L.; Srinivas, Tejaswinhi; Labus, Jennifer
Following sexual assault, little is known about how the social reactions women receive from informal supports and community-based providers relate to decisions to report to law enforcement. Among 213 diverse women who had disclosed a recent sexual assault to a community-based provider, 56% reported to law enforcement. Law enforcement reporting was associated with more positive (tangible aid) and less negative (distraction, being treated differently) reactions from informal supports and more tangible aid and less emotional support from community-based providers. Tangible aid from community-based providers predicted law enforcement reporting over the subsequent 9 months among women who had not initially reported.